Urban Poor Living: Accessing Their Ecosob Rights In Indonesia - Sakharina, Iin Karita; Daud, Aidir Amin; Hasrul, Muh.; Assidiq, Hasbi (International Journal of Psychosocial Rehabilitation, 2020)
The International Covenant on Economic, Social, and Cultural Rights has been ratified by Indonesia government through the Law of the Republic of Indonesia Number 11 Year 2005. A prosperous condition is a state of fulfillment of all necessities of life, especially those of a basic nature such as food, clothing, housing, education, and health care. Looking at comparisons in the two Big Cities, namely the West Jakarta Administrative City and Makassar City have different characteristics even though poverty rates are both showing a high enough number.